Required C × T Value for 5‐log Virus Inactivation at Full Scale. Issue 1 (1st January 2016) - Adelman, Michael J.; Phelps, Michael; Hadacek, Robert T.; Slosser, Oliver R.; Calvet, Simon; Oppenheimer, Joan; Borchardt, James H.
Abstract : The required free chlorine C × T (concentration times time) value for 5‐log virus inactivation was measured at a full‐scale water recycling plant through a suite of tracer, chlorine decay, and virusseeding tests on a baffled‐channel chlorine contactor. This plant produces fully nitrified, low‐turbidity filtered effluent. MS2 bacteriophage virus was seeded into the contactor at 10 6 pfu/mL, and inactivation of this virus, along with native coliform, were measured. A consistent MS2 inactivation rate >0.28 log‐L/mg‐min was observed for three different flows, consistent with other benchand pilot‐scale studies. At C × T values >22 mg‐min/L, the facility complied with California recycled water disinfection requirements by achieving >5.6‐log inactivation of MS2 and reducing 10 4 cfu/100 mL influent total coliform to <2.2 cfu/100 mL in the effluent. These results showed how complete nitrification and effective suspendedsolids removal allowed a full‐scale plant to realize favorable disinfection kinetics with free chlorine.